Poly(acrylic acid)/Poly(vinyl alcohol) Microarray Patches for Continuous Transdermal Delivery of Levodopa and Carbidopa: In Vitro and In Vivo Studies - Yaocun Li; Lalitkumar K. Vora; Jiawen Wang; Akmal Hidayat Bin Sabri; Andrew Graham; Helen O. McCarthy; Ryan F. Donnelly (MDPI AG, 2024)
Levodopa (LD) has been the most efficacious medication and the gold standard therapy for Parkinson's disease (PD) for decades. However, its long-term administration is usually associated with motor complications, which are believed to be the result of the fluctuating pharmacokinetics of LD following oral administration. Duodopa® is the current option to offer a continuous delivery of LD and its decarboxylase inhibitor carbidopa (CD); however, its administration involves invasive surgical procedures, which could potentially lead to lifelong complications, such as infection. Recently, dissolving microarray patches (MAPs) have come to the fore as an alternative that can bypass the oral administration route in a minimally invasive way. This work explored the potential of using dissolving MAPs to deliver LD and CD across the skin. An acidic polymer poly(acrylic acid) (PAA) was used in the MAP fabrication to prevent the potential oxidation of LD at neutral pH. The drug contents of LD and CD in the formulated dissolving MAPs were 1.82 ± 0.24 and 0.47 ± 0.04 mg/patch, respectively. The in vivo pharmacokinetic study using female Sprague-Dawley® rats (Envigo RMS Holding Corp, Bicester, UK) demonstrated a simultaneous delivery of LD and CD and comparable AUC values between the dissolving MAPs and the oral LD/CD suspension. The relative bioavailability for the dissolving MAPs was calculated to be approximately 37.22%. Accordingly, this work highlights the use of dissolving MAPs as a minimally invasive approach which could potentially bypass the gastrointestinal pathway and deliver both drugs continuously without surgery.